Nuevas citas de Catamblyrhynchus diadema en el Noroeste Argentino - Di Giacomo, Alejandro G. (1997)
The first record of the Plushcap ( Catamblyrhynchus diadema) for Salta province is given based in a collected specimen. New records for Jujuy province are reported. A immature plumage is described and information about the habits is discussed by means ofthe bibliography and field notes.